Gender Relationship with Decision Making Midwifery Services Facing Childbirth in Third Trimester Pregnant Women - Butar Butar, Maria; Palimbo, Adriana; Tambun, Madschen Sia Mei Ol Siska Selvija (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
The maternal mortality rate in Indonesia is categorized as high, caused by gender problems, namely the inability of women in making decisions related to self-readiness to face pregnancy, and the selection of helpers before childbirth. The purpose of the study was to determine the gender relationship regarding midwifery service decision-making, facing childbirth in third trimester pregnant women at the Malinau Health Center. Analytical observational research methods are used, with a cross-sectional design. The study sample was totaling 45 people. The data was analyzed with the Chi Square test. As a result, 23 respondents (51.11%) made inappropriate decisions about choosing midwifery services. Gender roles were 24 people (53.33%) in the ‘less’ category. There is a significant relationship between gender roles and decision-making for midwifery services facing childbirth in the third trimester of pregnant women at the Malinau Health Center in 2023, where the p-Value value = 0.001 < α = 0.05 is obtained. It was found that there was a significant relationship between gender roles and decision-making of midwifery services facing childbirth in third trimester pregnant women. Health workers should be more sensitive to gender issues, in carrying out midwifery care for patients